PENDEKATAN ETNOFOTOGRAFI DALAM KARYA FOTO DOKUMENTER - Purnama Yasa, Dewa (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2020)
Photos are considered as recordings of real events, actually taken. Camera footage seems to bring back what has happened in the past space and time to a different space and time. Doing ethnophotographic work is done changing ethnographic work done in the discipline of anthropology in general collecting data, conducting analysis, and arranging ethnography in a framework to answer specific (cultural) conversations. The main difference lies in the use of documentary photo media as part of the data, analysis, and results. Documentary photography works to see something deeper, not only see a reality from the surface, and this will train us to have a sensitivity to a social that occurs around us. Realities are taken later in photographs with the consent of a photographer.